Acreditación: un proceso vital para la internacionalización universitaria - Jiménez Arrunátegui, Yadira (2013)
History reference of universityaccreditation is presented in Latinoamericaregion, a reality expanding and puttingenergy into, as a demand of qualityassurance education based on teaching,searching and better services, pertinenceof study plans, greatest job chances forgraduates, setting out of cooperation andequality access agreements the benefitsbrought by international cooperation(CONEAU 2018).